Effect of build direction dependent grain structure on fatigue crack growth of biomedical Co–29Cr–6Mo alloy processed by laser powder bed fusion. (November 2021) - Anuar, A.; Guraya, T.; Chen, Z.W.; Ramezani, M.; San Sebastián-Ormazabal, M.
Abstract: Biomedical Co–29Cr–6Mo alloy is one of the alloys that are suitable for laser powder bed fusion (LPBF) additive manufacturing and as an implant material is often used in situations of critical and cyclic loading. Thus, fatigue crack growth (FCG) behaviour and resistance of the alloy processed by LPBF are an important consideration for dental and orthopaedic applications. In this study, FCG testing has been conducted to evaluate how build direction (BD) dependent grain/cell structure in relation to crack growth direction (CD), either CD⊥BD or CD//BD, affects FCG behaviour. It has been found that the threshold stress intensity factor (ΔKTh ) value is significantly higher and the values of c and m in Paris equation are slightly lower for CD//BD samples than the values for CD⊥BD samples, respectively. Failure analysis has revealed that the effects of the commonly known defect, lack of fusion, on both ΔKTh and FCG rate are weak. It has been identified that crack has mainly propagated in a transgranular and transcellular manner, consistent with the observation of the crack path being more torturous and with the higher crack growth resistance determined in CD//BD samples than in CD⊥BD samples. This will be further discussed linking the difference in the size of crack segment, which is BD and thus grain/cell length dependent, to the roughness-induced crack closure mechanism.